2018
DOI: 10.1039/c8dt00480c
|View full text |Cite
|
Sign up to set email alerts
|

Group 3 metal trihalide complexes with neutral N-donor ligands – exploring their affinity towards fluoride

Abstract: Fluorination of [ScCl3(Me3-tacn)] (Me3-tacn = 1,4,7-trimethyl-1,4,7-triazacyclononane) and [ScCl3(BnMe2-tacn)] (BnMe2-tacn = 1,4-dimethyl-7-benzyl-1,4,7-triazacyclononane) by Cl/F exchange with 3 mol. equiv. of anhydrous [NMe4]F in CH3CN solution yields the corresponding [ScF3(R3-tacn)] (R3 = Me3 or BnMe2). These are the first examples of scandium fluoride complexes containing neutral co-ligands. The fluorination occurs stepwise, and using a deficit of [NMe4]F produced [ScF2Cl(Me3-tacn)]. Attempts to fluorinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…This was also observed in the Group 13 (Al, Ga) and ScF 3 terpy complexes. 8,13 Among the complexes with Stability tests indicated that tacn derivatives bearing the FeF 3 fragment may be suitable for radiofluorination, and this was borne out by 18…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was also observed in the Group 13 (Al, Ga) and ScF 3 terpy complexes. 8,13 Among the complexes with Stability tests indicated that tacn derivatives bearing the FeF 3 fragment may be suitable for radiofluorination, and this was borne out by 18…”
Section: Discussionmentioning
confidence: 99%
“…6,7,12 We also investigated the transition metal fluorides using Sc(III), Y(III), La(III) and Lu(III). 13 Among these d-and f-block metal systems, only the [ScF 3 (RMe 2 -tacn)] (R = Me, Bn) were successfully synthesised through Cl/F halide exchange reactions. [ScF 3 (BnMe 2 -tacn)] was identified as a promising system for future 18 F-radiolabelling, although, in contrast to the Group 13 systems, it could only be obtained from the trichloride analogue under anhydrous conditions using [NMe 4 ]F or Me 3 SnF as the fluoride source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular structure of [ScCl 3 (ptpy)] is quite similar to trichlorido(2,2′:6′,2′′‐terpyridine)scandium (crystallizing in space group P 2 1 / n ), the main difference between two complexes being the additional phenyl ring in ptpy [32] . Due to the small ionic radius of trivalent scandium, no additional molecules, such as solvent molecules, are coordinated to the metal center in the resulting [ScCl 3 (ptpy)] complex, unlike with trivalent lanthanides, which form complexes of general formula [LnCl 3 (ptpy)(py)], in which the metal ion coordination sphere forms a distorted pentagonal bipyramid [28] .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have presented two series of lanthanide coordination polymers and complexes including organic ligand sensitized 4f‐4f emission of NIR and visible emitters [28] . Despite the wide usage of terpyridine and other tridentate N‐ligands in the coordination chemistry of lanthanides, only a few examples of coordination compounds obtained with scandium have been published, so far: with 4‐amino‐bis(2,6‐(2‐pyridyl))‐1,3,5‐triazine [29] and 2,6‐bis(4‐isopropyl‐4,5‐dihydro‐1,3‐oxazol‐2‐yl)pyridine, [30] which have an N N N coordination site similar to terpyridine, and two with 2,2′:6′,2′′‐terpyridine itself [31,32] . Other examples are in situ generated trivalent scandium complexes with terpyridine or related molecules for catalysis, [33,34] or monitoring the changes of organic‐based luminescence of 2,3,5,6‐tetrakis(2‐pyridyl)pyrazine in presence of Sc 3+ and other metal ions [35,36] .…”
Section: Introductionmentioning
confidence: 99%